Reductions in cortical alpha activity, enhancements in neural responses and impaired gap detection caused by sodium salicylate in awake guinea pigs - Berger, Joel I.; Coomber, Ben; Wallace, Mark N.; Palmer, Alan R. (Wiley, 2017)
Tinnitus chronically affects between 10–15% of the population but, despite its prevalence, the underlying mechanisms are still not properly understood. One experimental model involves administration of high doses of sodium salicylate, as this is known to reliably induce tinnitus in both humans and animals. Guinea pigs were implanted with chronic electrocorticography (ECoG) electrode arrays, with silver-ball electrodes placed on the dura over left and right auditory cortex. Two more electrodes were positioned over the cerebellum to monitor auditory brainstem responses (ABRs). We recorded resting-state and auditory evoked neural activity from awake animals before and 2 h following salicylate administration (350 mg/kg; i.p.). Large increases in click-evoked responses (> 100%) were evident across the whole auditory cortex, despite signiﬁcant reductions in wave I ABR amplitudes (in response to 20 kHz tones), which are indicative of auditory nerve activity. In the same animals, signiﬁcant decreases in 6–10 Hz spontaneous oscillations (alpha waves) were evident over dorsocaudal auditory cortex. We were also able to demonstrate for the ﬁrst time that cortical evoked potentials can be inhibited by a preceding gap in background noise [gap-induced pre-pulse inhibition (PPI)], in a similar fashion to the gap-induced inhibition of the acoustic startle reﬂex that is used as a behavioural test for tinnitus. Furthermore, 2 h following salicylate administration, we observed signiﬁcant deﬁcits in PPI of cortical responses that were closely aligned with signiﬁcant deﬁcits in behavioural responses to the same stimuli. Together, these data are suggestive of neural correlates of tinnitus and oversensitivity to sound (hyperacusis).